Design and development of ornithopter and experimental analysis of flapping rate under various operating conditions. (2018) - Vignesh, S.; Arulshri, K.P.; SyedSajith, S.; Kathiresan, S.; Boopathi, S.; Dinesh Babu, P.
Abstract: This research work deals with an economic design of the ornithopter which is a type of aircraft that flies by flapping its wings. The process of designing ornithopter involves flapping mechanism. The ornithopter developed is subjected to an investigation involving the analysis of flapping rate under various operating conditions. The analysis of flapping rate involving ornithopter is a novel approach, as the research related to this area is found to be very limited. The variation in number of turns winded up for three possible trials have been performed for the elastic band in the ornithopter with and without the application of lubricant. The time and flapping rate for each trial has been measured and influence effects were analysed from the average time and flapping rate. It was found that the maximum number of turns were increased from 100 to 200, in the case of elastic band with lubrication.